KAJIAN DAYA DUKUNG LAHAN PERTANIAN DALAM MENUNJANG SWASEMBADA PANGAN DI KABUPATEN MINAHASA SELATAN - Celsius ., Talumingan; Sherly G. Jocom (Sam Ratulangi University, 2017)
The general objective of this research is to know how much agricultural land capacity in support of food self-sufficiency in South Minahasa regency. In particular, this study aims to know the area / region in South Minahasa regency which became the basis of the carrying capacity of food security, so that the area becomes a base bias related to population increases. Adadpun benefits of this research is expected to contribute ideas for the South Minahasa local governments and agencies involved in food security in order to address land use so as not to cause problems carrying capacity of land to food self-sufficiency. Contributing of this research is to the development of economic knowledge of the area and land resources. To achieve the objectives to be achieved in the research used a method that determines the level of the carrying capacity of crop lands with the concept of combination of theory Odum, Cristeiler, E Howard and Issard. This study found that the overall average of carrying capacity of crop lands in South Minahasa Regency is 0,414. It means that existing agricultural lands in South Minahasa Regency has not been able to perform self-sufficiency and has not been able to provide adequate food.